Fatalities of stowaways traveling in airplane wheel wells. (September 2018) - Plenzig, Stefanie; Held, Hannelore; Holz, Franziska; Kals, Theresa; Verhoff, Marcel A.
Highlights: This study examined the fatalities of stowaways traveling in airplane wheel wells. Possible causes of death are addressed and discussed. Pertinent technical aspects of airplanes are taken into consideration. The finding specifics and relevance of discovery site investigations are described. Abstract: The earliest mention of a stowaway in the wheel well of an airplane dates back to 1947: A 30-year-old man chose this mode of travel for a trip from Lisbon to Brazil and survived (Véronneau et al., 1996). In a retrospective study, we evaluated cases with lethal outcome of stowaways in airplane wheel wells by focusing on forensic autopsy results, in particular, in regard to hypothermia, hypoxia, and injuries. In addition, the flight routes, flight altitudes, and flight durations were analyzed. Using the forensik ® program, a search of all the autopsies performed between 1994–2017 at the Institute of Legal Medicine in Frankfurt am Main, Germany, was conducted, using the key words "airplane, " "flights, " and "wheel well." All of the thus retrieved autopsy reports, medicolegal expert reports, and police investigation reports were then evaluated. Five cases were included in our study. The decedents were all men, aged between 14 and 26 years. Four of the decedents had been discovered at the Frankfurt Main airport within airplane wheel wells; the fifth man had been discovered in a woods underlying one of the flight approach paths to the airport. Two stowaways had died of hypoxic asphyxiation, possibly in conjunction with hypothermia as a contributing factor. One stowaway died of the polytrauma he sustained when he was crushed by retracting landing gear. For a further stowaway, the cause of death could not be macroscopically determined at autopsy. In one case, only an external postmortem examination had been performed, without autopsy. Analysis of the flight routes, altitudes, and durations showed that the flights had been international flights, the flight altitudes had varied between 7000 m (∼23, 000 ft) und 11, 000 m (∼36, 000 ft), and the flight duration had been between 4 and 9.5 h. At high altitudes, the ambient conditions in wheel wells, which are not pressurized, are rarely survived by stowaways, with hypoxic asphyxiation likely posing greater peril than hypothermia. Further dangers are that of being crushed by retracting landing gear after takeoff, or of falling out of a wheel well, from a great height, when the landing gear is deployed. When it appears conceivable that a stowaway may have fallen from an aircraft wheel well during landing or takeoff, an autopsy and discovery scene investigation are essential to reconstructing the course of events.